MANIFESTASI IDA SANG HYANG WIDHI WASA DALAM GEGURITAN I PUNYAN GADUNG NYUJUR AMBARA: ANALISIS SEMIOTIK - Sri Wisnawi, Ni Made Dewi (Humanis; Volume 5. No. 1. Oktober 2013, 2013)
Geguritan I Punyan Gadung Nyujur Ambara, representing Traditional Bali belleslettres which is in form of narrative poem. This Skripsi entitle the " Manifestasi Ida Sang Hyang Widhi Wasa in Geguritan I Punyan Gadung Nyujur Ambara : Analyse the Semiotic". Result from this research earn the description about structure and analyse the semiotik which implied in the Geguritan I Punyan Gadung Nyujur Ambara. Geguritan I Punyan Gadung Nyujur Ambara analysed by using theory semiotic. To water down the analysis used by a method consisted of by some step, that is: ( 1) ready phase of data by using method correct reading and interview and technics used by technics of record-keeping and technique record, ( 2) phase analyse the data, using method qualitative and technics used by analytic descriptive technics, and ( 3) phase of result of data analysis using the informal formal method assisted which supported by inductive thinking technics. Expression of Structure of Geguritan I Punyan Gadung Nyujur Ambara as belleslettres which is in form of traditional poem cover the microstructure and macrostructure. Microstructure cover the aspect gramatikal with the reached result cover the reference, substitution, and konjungtion, later then reached aspect leksikal in this research cover the repeatation, antonimi, and colocation. Macrostructure which consist theme developing Geguritan I Punyan Gadung Nyujur Ambara that is with the theme " Sradha Bakti". Analysis Semiotic in Geguritan I Punyan Gadung Nyujur Ambara consist of three elements such as iconiq element, indexing, and symbolic.
Keywords: structure, micro structure, macro stucture, ikoniq, symbolic, and indexing